Down jacket fabric containing graphene fibers and preparation method thereof

By using modified graphene oxide composite fibers and modified nano-silica materials in down jacket fabrics, the problem of insufficient antibacterial and warm-keeping performance of existing nylon fabrics is solved, and the far-infrared warm-keeping, antibacterial and wear-resistant properties of the fabrics are improved.

CN119754037AActive Publication Date: 2025-04-04SHAOXING FUHAO TEXTILE TECH CO LTD

Patent Information

Application Number
CN202510041178.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing nylon fabrics have shortcomings in antibacterial properties and warm-keeping properties, which cannot effectively inhibit bacterial growth and are not warm-keeping to provide sufficient heat protection in cold weather.

Method used

Graphene composite fibers are prepared by mixing modified graphene oxide, maleic anhydride, SEBS and nylon slices for mixing, extrusion granulation and melt spinning, and interwoven with polyester fibers to form a down jacket fabric containing graphene fibers. The fabric improves antibacterial and warmth properties through the use of modified nanosilicon dioxide and polyhexamethylene biguanide hydrochloride.

Benefits of technology

It has achieved the improvement of the far-infrared warm and antibacterial properties of the fabric, significantly improved the functionality and safety of the down jacket fabric, and enhanced the wear resistance of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236992220000161
    Figure BDA0005236992220000161
  • Figure BDA0005236992220000171
    Figure BDA0005236992220000171
  • Figure BDA0005236992220000172
    Figure BDA0005236992220000172
Patent Text Reader

Abstract

The invention relates to the technical field of functional fabric preparation, and discloses a graphene fiber-containing down jacket fabric and a preparation method thereof.The graphene fiber-containing down jacket fabric is prepared by mixing graphene oxide and gelatin, performing vacuum freeze drying treatment to form porous aerogel, and then modifying the composite graphene oxide aerogel to obtain the graphene fiber-containing down jacket fabric. The tetraphenyl ethylene is grafted on the composite aerogel, so that the warm-keeping property and the wear-resisting property of the fabric are improved; the nano silicon dioxide is modified, the hydroxyl-terminated polybutadiene is grafted on the nano silicon dioxide, and the two ends of the hydroxyl-terminated polybutadiene contain hydroxyl groups, so that the dispersing performance of the nano silicon dioxide in the finishing liquid can be improved, and agglomeration is avoided; meanwhile, the hydroxyl-terminated polybutadiene molecular structure contains an alkyl long-chain structure, and the alkyl long-chain structure has good flexibility and phase change energy storage performance, so that the thermal insulation performance and wear resistance of the fabric are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional fabric preparation, and in particular to a down jacket fabric containing graphene fibers and a preparation method thereof. Background Art

[0002] Nylon fabrics are widely favored in the production of down jacket fabrics due to their excellent lightness and warmth retention. However, despite the many advantages of nylon materials, their antibacterial properties are poor and cannot effectively inhibit the growth of bacteria. In addition, the thermal insulation performance of nylon is also considered to be at an average level, which may not provide sufficient thermal protection in cold weather. Therefore, it is particularly important to research and develop down jacket fabrics with far-infrared thermal insulation and antibacterial properties to improve the functionality and safety of the entire down jacket.

[0003] As an emerging functional material, graphene has excellent far-infrared emission and antibacterial properties due to its unique structure, which makes it have great potential in improving the functionality of down jacket fabrics. Although graphene performs well in functional materials, it is an inorganic nanopowder with poor dispersibility in solution, which easily causes aggregation, hindering its application in the textile industry.

[0004] Chinese patent document CN 113995189 A discloses a method for preparing graphene antibacterial down jacket fabric, which comprises the following steps: firstly treating graphene with gallic acid or citric acid, then adding an adhesive, and then subjecting the modified graphene to a viscose fiber or a polytetrafluoroethylene fiber through a hot pressing process, and finally blending the modified graphene with a natural fiber to obtain the graphene antibacterial down jacket fabric. However, both gallic acid and citric acid are weak acids, and the active groups on the surface of graphene are very few, and the reaction performance between them is poor. Therefore, it is difficult to effectively modify graphene with gallic acid or citric acid, and the performance of the prepared down jacket fabric still needs to be further improved. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a down jacket fabric containing graphene fibers and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0008] S1. Preparation of graphene composite fibers

[0009] The modified graphene oxide, maleic anhydride grafted SEBS and nylon chips are mixed and extruded into granules to obtain master batches, which are then melt-spun to obtain graphene composite fibers.

[0010] In this step, the mass ratio of modified graphene oxide, maleic anhydride grafted SEBS and nylon chips is 3-6:1-2:100. In some embodiments of the present invention, for example, 3:1:100, 3:1.5:100, 4:1:100, 4:2:100, 6:1:100, 6:2:100 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] Specifically, the preparation method of the modified graphene oxide is as follows:

[0012] S11, ultrasonically dispersing graphene oxide in deionized water, adding sodium carboxymethyl cellulose, stirring and mixing evenly, then adding gelatin, stirring at 85-90° C. for 2-4 hours, ultrasonically dispersing for 30-60 minutes, vacuum freeze-drying, grinding and sieving, to obtain a composite graphene oxide aerogel;

[0013] S12, dispersing the composite graphene oxide aerogel in an ethanol aqueous solution, then adding vinyl triethoxysilane thereto, stirring at room temperature for 1-2 hours, filtering, washing, and drying to obtain a vinyl-modified composite aerogel;

[0014] S13, dispersing the vinyl modified composite aerogel in toluene, then adding tetraphenylethylene and benzoyl peroxide thereto, heating and stirring at 70-90° C. for reaction for 3-5 hours, and after the reaction is completed, filtering, washing, drying, grinding and sieving to obtain modified graphene oxide.

[0015] On the basis of the above technical scheme, specifically, in step S11, the mass ratio of graphene oxide, sodium carboxymethyl cellulose and gelatin is 10-15:4-8:5-10. For example, 10:4:5, 10:6:8, 10:8:10, 12:4:5, 12:4:8, 12:6:8, 12:8:10, 15:4:5, 15:5:10, and 15:8:10 can be selected, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0016] On the basis of the above technical scheme, specifically, in step S12, the mass ratio of the composite graphene oxide aerogel and vinyltriethoxysilane is 10-15:1-3, for example, 10:1, 10:2, 10:3, 12:1, 12:2, 12:3, 15:1, 15:2, 15:3 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] On the basis of the above technical scheme, specifically, in step S13, the mass ratio of the vinyl-modified composite aerogel, tetraphenylethylene and benzoyl peroxide is 8-12:3-6:0.5-1, for example, 8:3:0.5, 8:5:0.8, 8:6:1, 10:3:0.5, 10:5:0.8, 10:5:1, 12:6:0.5, 12:6:1 can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] In this step, graphene oxide and gelatin are mixed and subjected to vacuum freeze-drying treatment to form a porous aerogel. At the same time, sodium carboxymethyl cellulose is added to improve the pore size distribution of the aerogel, thereby improving the thermal insulation effect of the aerogel. Then, the composite graphene oxide aerogel is double-bonded modified, and tetraphenylethylene is grafted onto the composite aerogel through an addition reaction between the double bonds. Tetraphenylethylene contains a large amount of aromatic structures, which can significantly enhance the absorption of ultraviolet light, visible light and near-infrared short-wave regions, thereby achieving a better thermal insulation effect.

[0019] S2. Preparation of fabric base fabric

[0020] The graphene composite fiber and polyester fiber are mixed, and then interwoven with the warp and weft yarns to obtain the fabric base cloth.

[0021] In this step, the mass ratio of graphene composite fiber to polyester fiber is 1-2:1-2, for example, 1:1, 1:2, 1.5:1, 1.5:2, 2:1, 2:1.5 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In this step, the linear density of the warp yarn is 15-20tex, and the linear density of the weft yarn is 15-20tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 360-365 yarns / 10cm, and the weft yarn density is 325-330 yarns / 10cm.

[0023] S3. Preparation of down jacket fabric

[0024] The fabric base fabric is subjected to padding treatment in a finishing liquid, and then the padding fabric base fabric is baked, washed and dried to obtain a down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 60-80 parts of aqueous polyurethane emulsion, 4-8 parts of blocked isocyanate cross-linking agent, 2-4 parts of modified nano-silica, 2-4 parts of polyhexamethylene biguanide hydrochloride, 0.5-1 part of sodium dodecylbenzene sulfonate, and 10-15 parts of deionized water.

[0025] In this step, the preparation method of modified nano silicon dioxide is as follows:

[0026] S31, dispersing 8-12 parts of nano-silica in an ethanol aqueous solution, then adding 1-3 parts of vinyltriethoxysilane thereto, stirring at room temperature for 1-2 hours, filtering, washing, and drying to obtain vinyl-modified nano-silica;

[0027] S32, dispersing vinyl modified nano silica in an organic solvent DMF, then adding terminal hydroxyl polybutadiene and benzoyl peroxide thereto, heating and stirring at 60-80°C for reaction for 2-5h, after the reaction is completed, filtering, washing, drying, grinding and sieving to obtain modified nano silica.

[0028] On the basis of the above technical scheme, specifically, in step S32, the mass ratio of vinyl-modified nano-silica, terminal hydroxyl polybutadiene and benzoyl peroxide is 5-10:2-4:0.5-1, for example, 5:2:0.5, 5:3:0.8, 5:4:1, 8:2:0.5, 8:3:0.8, 8:4:0.8, 8:4:1, 10:3:0.5, 10:4:1 can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] On the basis of the above technical solution, the padding liquid rate of the fabric base fabric after padding treatment is 70-80%.

[0030] On the basis of the above technical solution, the baking temperature is 120-150°C and the drying time is 3-5 minutes.

[0031] In this step, the terminal hydroxyl polybutadiene is grafted onto the nano silica by modifying the nano silica. The two ends of the terminal hydroxyl polybutadiene contain hydroxyl groups, which can improve the dispersion performance of the nano silica in the finishing liquid and avoid agglomeration. The terminal hydroxyl polybutadiene molecular structure contains an alkyl long chain structure, which has good flexibility and phase change energy storage performance, and further increases the thermal insulation performance of the fabric. When the fabric fiber and other objects rub against each other, the alkyl long chain structure on the surface of the fabric undergoes extrusion, denaturation and other movements, thereby reducing the friction coefficient of the fabric fiber, preventing fabric loss, and further improving the wear resistance of the fabric.

[0032] In this step, polyhexamethylene biguanide hydrochloride mainly plays an antibacterial role.

[0033] In this step, the blocked isocyanate cross-linking agent can stably coexist with active groups such as hydroxyl and amino groups for a long time at room temperature. After heat treatment, the isocyanate cross-linking agent releases -NCO groups and reacts with hydroxyl, amino and other groups to form cross-links, so that the effective ingredients in the finishing liquid can be firmly attached to the surface of the fabric. After the fabric is washed many times, the effective ingredients on its surface will not be easily peeled off, so that the fabric can maintain excellent functionality for a long time.

[0034] The present invention also provides a down jacket fabric containing graphene fibers prepared by the above preparation method.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The down jacket fabric containing graphene fibers provided by the present invention is prepared by mixing graphene oxide and gelatin, and then subjecting the mixture to a vacuum freeze-drying process to form a porous aerogel. Meanwhile, sodium carboxymethyl cellulose is added to improve the pore size distribution of the aerogel, thereby improving the thermal insulation effect of the aerogel. Then, the composite graphene oxide aerogel is double-bond modified, and tetraphenylethylene is grafted onto the composite aerogel through an addition reaction between the double bonds. The tetraphenylethylene contains a large amount of aromatic structures, which can significantly enhance the absorption of ultraviolet light, visible light, and near-infrared short-wave regions, thereby achieving a better thermal insulation effect. Meanwhile, the presence of the aromatic structure also improves the wear resistance of the fabric to a certain extent.

[0037] (2) The present invention modifies nano-silicon dioxide and grafts terminal hydroxyl polybutadiene onto the nano-silicon dioxide. The terminal hydroxyl polybutadiene contains hydroxyl groups at both ends, which can improve the dispersion performance of the nano-silicon dioxide in the finishing liquid and avoid agglomeration. The terminal hydroxyl polybutadiene contains an alkyl long chain structure in its molecular structure. The alkyl long chain structure has good flexibility and phase change energy storage performance, which further increases the thermal insulation performance of the fabric. When the fabric fiber rubs against other objects, the alkyl long chain structure on the surface of the fabric undergoes extrusion, denaturation and other movements, thereby reducing the friction coefficient of the fabric fiber, preventing fabric loss, and further improving the wear resistance of the fabric.

[0038] (3) The blocked isocyanate crosslinking agent provided by the present invention can coexist stably with active groups such as hydroxyl and amino groups for a long time at room temperature. After heat treatment, the isocyanate crosslinking agent releases -NCO groups and reacts with hydroxyl, amino and other groups to form crosslinks, so that the effective ingredients in the finishing liquid can be firmly attached to the surface of the fabric. After the fabric is washed many times, the effective ingredients on its surface will not be easily peeled off, so that the fabric can maintain excellent functionality for a long time. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0040] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0041] The graphene oxide used in the present invention has a CAS number of 1034343-98-0, a thickness of 0.55-1.2 nm, and a number of 1-3 layers, which is purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd.; the model of maleic anhydride grafted SEBS is XYJ12902, which is purchased from Dongguan Xingyuan Chemical Co., Ltd.; the model of nylon slices is PA6; polyester fiber is purchased from Hangzhou Yongxing Chemical Fiber Co., Ltd.; the model of water-based polyurethane emulsion is PU667, which is purchased from Nanjing Chuhai New Materials Technology Co., Ltd.; the model of blocked isocyanate crosslinker is JL-WEB, which is purchased from Suzhou Jinyunlai Textile Auxiliary Agent Co., Ltd.; the average particle size of nano-silicon dioxide is 60 nm; the CAS number of polyhexamethylene biguanide hydrochloride is 32289-58-0, which is purchased from Hubei Yamade Biomedical Co., Ltd.; the CAS number of hydroxy-terminated polybutadiene is 69102-90-5, which is purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd.

[0042] Example 1

[0043] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0044] S1, 3 parts of modified graphene oxide, 1 part of maleic anhydride grafted SEBS and 100 parts of nylon chips are mixed, extruded and granulated to obtain a masterbatch, and then melt-spinned to obtain a graphene composite fiber;

[0045] Wherein, the preparation method of modified graphene oxide is as follows:

[0046] 10 g of graphene oxide was ultrasonically dispersed in 150 g of deionized water, 4 g of sodium carboxymethyl cellulose was added, and the mixture was stirred and mixed evenly, followed by adding 5 g of gelatin, stirring at 85 ° C for 4 h, and then ultrasonically dispersed for 30 min, vacuum freeze-dried, and ground through a 1200 mesh sieve to obtain a composite graphene oxide aerogel;

[0047] 10 g of composite graphene oxide aerogel was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 1 h, filtered, washed, and dried to obtain a vinyl-modified composite aerogel;

[0048] 8 g of vinyl-modified composite aerogel was dispersed in 100 mL of toluene, and then 3 g of tetraphenylethylene and 0.5 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 70°C for 5 h. After the reaction was completed, the modified graphene oxide was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0049] S2. The graphene composite fiber and the polyester fiber are mixed in a mass ratio of 1:1, and then interwoven by warp yarn and weft yarn, wherein the linear density of the warp yarn is 20tex, and the linear density of the weft yarn is 15tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 360 yarns / 10cm, and the weft yarn density is 325 yarns / 10cm, to obtain a fabric base fabric;

[0050] S3, padding the fabric base fabric in the finishing liquid, the bath ratio is 1-20, the padding liquid rate of the fabric base fabric after padding is 75%, and then baking the fabric base fabric after padding, the baking temperature is 120 ° C, the drying time is 5min, and then washing with deionized water, and then drying at 60 ° C, that is, obtaining a down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 60 parts of aqueous polyurethane emulsion, 4 parts of blocked isocyanate crosslinking agent, 2 parts of modified nano-silica, 2 parts of polyhexamethylene biguanide hydrochloride, 0.5 parts of sodium dodecylbenzene sulfonate, and 10 parts of deionized water;

[0051] Wherein, the preparation method of modified nano silicon dioxide is as follows:

[0052] 8 g of nano-silica was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 1 h, filtered, washed, and dried to obtain vinyl-modified nano-silica;

[0053] 5 g of vinyl-modified nano-silica was dispersed in 100 mL of organic solvent DMF, and then 2 g of terminal hydroxyl polybutadiene and 0.5 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 60°C for 5 h. After the reaction was completed, the modified nano-silica was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0054] Example 2

[0055] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0056] S1, mixing 6 parts of modified graphene oxide, 2 parts of maleic anhydride grafted SEBS and 100 parts of nylon chips, extruding and granulating to obtain a masterbatch, and then melt-spinning to obtain a graphene composite fiber;

[0057] Wherein, the preparation method of modified graphene oxide is as follows:

[0058] 12 g of graphene oxide was ultrasonically dispersed in 150 g of deionized water, 6 g of sodium carboxymethyl cellulose was added, and the mixture was stirred and mixed evenly, followed by adding 8 g of gelatin, stirring at 90 ° C for 2 h, and then ultrasonically dispersed for 60 min, vacuum freeze-dried, and ground through a 1200 mesh sieve to obtain a composite graphene oxide aerogel;

[0059] 15 g of composite graphene oxide aerogel was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 3 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 1 h, filtered, washed, and dried to obtain a vinyl-modified composite aerogel;

[0060] 10 g of vinyl-modified composite aerogel was dispersed in 100 mL of toluene, and then 5 g of tetraphenylethylene and 0.8 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 90°C for 3 h. After the reaction was completed, the modified graphene oxide was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0061] S2. The graphene composite fiber and the polyester fiber are mixed in a mass ratio of 1.5:1, and then interwoven by warp yarn and weft yarn, wherein the linear density of the warp yarn is 20tex, and the linear density of the weft yarn is 15tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 360 yarns / 10cm, and the weft yarn density is 325 yarns / 10cm, to obtain a fabric base cloth;

[0062] S3, padding the fabric base fabric in the finishing liquid, the bath ratio is 1-20, the padding liquid rate of the fabric base fabric after padding is 75%, and then baking the fabric base fabric after padding, the baking temperature is 120 ° C, the drying time is 5min, and then washing with deionized water, and then drying at 60 ° C, that is, obtaining a down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 80 parts of aqueous polyurethane emulsion, 6 parts of blocked isocyanate crosslinking agent, 4 parts of modified nano-silica, 4 parts of polyhexamethylene biguanide hydrochloride, 1 part of sodium dodecylbenzene sulfonate, and 15 parts of deionized water;

[0063] Wherein, the preparation method of modified nano silicon dioxide is as follows:

[0064] 12 g of nano-silica was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 3 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 2 h, filtered, washed, and dried to obtain vinyl-modified nano-silica;

[0065] 8 g of vinyl-modified nano-silica was dispersed in 100 mL of organic solvent DMF, and then 3 g of terminal hydroxyl polybutadiene and 0.8 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 80°C for 2 h. After the reaction was completed, the modified nano-silica was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0066] Example 3

[0067] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0068] S1, 4 parts of modified graphene oxide, 1.5 parts of maleic anhydride grafted SEBS and 100 parts of nylon chips are mixed and extruded to obtain master batches, and then melt-spinned to obtain graphene composite fibers;

[0069] Wherein, the preparation method of modified graphene oxide is as follows:

[0070] 15 g of graphene oxide was ultrasonically dispersed in 150 g of deionized water, 8 g of sodium carboxymethyl cellulose was added, and the mixture was stirred and mixed evenly, followed by adding 10 g of gelatin, stirring at 90° C. for 2 h, and then ultrasonically dispersed for 60 min, and then freeze-dried in vacuum, and ground through a 1200 mesh sieve to obtain a composite graphene oxide aerogel;

[0071] 12 g of composite graphene oxide aerogel was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 2 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 1 h, filtered, washed, and dried to obtain a vinyl-modified composite aerogel;

[0072] 12 g of vinyl-modified composite aerogel was dispersed in 100 mL of toluene, and then 6 g of tetraphenylethylene and 1 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 80°C for 4 h. After the reaction was completed, the modified graphene oxide was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0073] S2. The graphene composite fiber and the polyester fiber are mixed in a mass ratio of 1:1.5, and then interwoven by warp and weft, wherein the linear density of the warp is 20tex, and the linear density of the weft is 15tex; the specific weaving process is: the warp and weft are interwoven one above and one below each other in a plain weave manner, the warp density is 360 yarns / 10cm, and the weft density is 325 yarns / 10cm, to obtain a fabric base fabric;

[0074] S3, padding the fabric base fabric in the finishing liquid, the bath ratio is 1-20, the padding liquid rate of the fabric base fabric after padding is 75%, and then baking the fabric base fabric after padding, the baking temperature is 150 ° C, the drying time is 3min, and then washing with deionized water, and then drying at 60 ° C, that is, obtaining a down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 70 parts of aqueous polyurethane emulsion, 5 parts of blocked isocyanate crosslinking agent, 3 parts of modified nano-silica, 2 parts of polyhexamethylene biguanide hydrochloride, 0.8 parts of sodium dodecylbenzene sulfonate, and 12 parts of deionized water;

[0075] Wherein, the preparation method of modified nano silicon dioxide is as follows:

[0076] Disperse 10 g of nano-silica in 100 mL of 80 wt% ethanol aqueous solution, then add 2 g of vinyl triethoxysilane, stir at room temperature for 2 h, filter, wash, and dry to obtain vinyl-modified nano-silica;

[0077] 10 g of vinyl-modified nano-silica was dispersed in 100 mL of organic solvent DMF, and then 4 g of terminal hydroxyl polybutadiene and 1 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 80°C for 2 h. After the reaction was completed, the modified nano-silica was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0078] Comparative Example 1

[0079] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0080] S1, mixing 3 parts of graphene oxide, 1 part of maleic anhydride grafted SEBS and 100 parts of nylon chips, extruding and granulating to obtain a masterbatch, and then melt-spinning to obtain a graphene composite fiber;

[0081] S2. The graphene composite fiber and the polyester fiber are mixed in a mass ratio of 1:1, and then interwoven by warp yarn and weft yarn, wherein the linear density of the warp yarn is 20tex, and the linear density of the weft yarn is 15tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 360 yarns / 10cm, and the weft yarn density is 325 yarns / 10cm, to obtain a fabric base fabric;

[0082] S3. The fabric base fabric is immersed in the finishing liquid for padding treatment, the bath ratio is 1-20, the padding liquid rate of the fabric base fabric after the padding treatment is 75%, and then the fabric base fabric after the padding treatment is baked at a baking temperature of 120°C and a drying time of 5 minutes, and then washed with deionized water, and then dried at 60°C to obtain down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 60 parts of aqueous polyurethane emulsion, 4 parts of blocked isocyanate cross-linking agent, 2 parts of nano-silica, 2 parts of polyhexamethylene biguanide hydrochloride, 0.5 parts of sodium dodecylbenzene sulfonate, and 10 parts of deionized water.

[0083] Compared with Example 1, in Comparative Example 1, graphene oxide and nano-silicon dioxide were not modified.

[0084] Comparative Example 2

[0085] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0086] S1, mixing 3 parts of graphene oxide, 1 part of maleic anhydride grafted SEBS and 100 parts of nylon chips, extruding and granulating to obtain a masterbatch, and then melt-spinning to obtain a graphene composite fiber;

[0087] S2. The graphene composite fiber and the polyester fiber are mixed in a mass ratio of 1:1, and then interwoven by warp yarn and weft yarn, wherein the linear density of the warp yarn is 20tex, and the linear density of the weft yarn is 15tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 360 yarns / 10cm, and the weft yarn density is 325 yarns / 10cm, to obtain a fabric base fabric;

[0088] S3, padding the fabric base fabric in the finishing liquid, the bath ratio is 1-20, the padding liquid rate of the fabric base fabric after padding is 75%, and then baking the fabric base fabric after padding, the baking temperature is 120 ° C, the drying time is 5min, and then washing with deionized water, and then drying at 60 ° C, that is, obtaining a down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 60 parts of aqueous polyurethane emulsion, 4 parts of blocked isocyanate crosslinking agent, 2 parts of modified nano-silica, 2 parts of polyhexamethylene biguanide hydrochloride, 0.5 parts of sodium dodecylbenzene sulfonate, and 10 parts of deionized water;

[0089] Wherein, the preparation method of modified nano silicon dioxide is as follows:

[0090] 8 g of nano-silica was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 1 h, filtered, washed, and dried to obtain vinyl-modified nano-silica;

[0091] 5 g of vinyl-modified nano-silica was dispersed in 100 mL of organic solvent DMF, and then 2 g of terminal hydroxyl polybutadiene and 0.5 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 60°C for 5 h. After the reaction was completed, the modified nano-silica was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0092] Compared with Example 1, in Comparative Example 2, no modification treatment was performed on graphene oxide.

[0093] Comparative Example 3

[0094] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0095] S1, 3 parts of modified graphene oxide, 1 part of maleic anhydride grafted SEBS and 100 parts of nylon chips are mixed, extruded and granulated to obtain a masterbatch, and then melt-spinned to obtain a graphene composite fiber;

[0096] Wherein, the preparation method of modified graphene oxide is as follows:

[0097] 10 g of graphene oxide was ultrasonically dispersed in 150 g of deionized water, 4 g of sodium carboxymethyl cellulose was added, and the mixture was stirred and mixed evenly, followed by adding 5 g of gelatin, stirring at 85 ° C for 4 h, and then ultrasonically dispersed for 30 min, vacuum freeze-dried, and ground through a 1200 mesh sieve to obtain a composite graphene oxide aerogel;

[0098] 10 g of composite graphene oxide aerogel was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 1 h, filtered, washed, and dried to obtain a vinyl-modified composite aerogel;

[0099] 8 g of vinyl-modified composite aerogel was dispersed in 100 mL of toluene, and then 3 g of tetraphenylethylene and 0.5 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 70°C for 5 h. After the reaction was completed, the modified graphene oxide was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0100] S2. The graphene composite fiber and the polyester fiber are mixed in a mass ratio of 1:1, and then interwoven by warp yarn and weft yarn, wherein the linear density of the warp yarn is 20tex, and the linear density of the weft yarn is 15tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 360 yarns / 10cm, and the weft yarn density is 325 yarns / 10cm, to obtain a fabric base fabric;

[0101] S3. The fabric base fabric is immersed in the finishing liquid for padding treatment, the bath ratio is 1-20, the padding liquid rate of the fabric base fabric after the padding treatment is 75%, and then the fabric base fabric after the padding treatment is baked at a baking temperature of 120°C and a drying time of 5 minutes, and then washed with deionized water, and then dried at 60°C to obtain down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 60 parts of aqueous polyurethane emulsion, 4 parts of blocked isocyanate cross-linking agent, 2 parts of nano-silica, 2 parts of polyhexamethylene biguanide hydrochloride, 0.5 parts of sodium dodecylbenzene sulfonate, and 10 parts of deionized water.

[0102] Compared with Example 1, in Comparative Example 3, no modification treatment was performed on the nano-silicon dioxide.

[0103] Comparative Example 4

[0104] A method for preparing a down jacket fabric containing graphene fibers comprises the following steps:

[0105] S1, 3 parts of modified graphene oxide, 1 part of maleic anhydride grafted SEBS and 100 parts of nylon chips are mixed, extruded and granulated to obtain a masterbatch, and then melt-spinned to obtain a graphene composite fiber;

[0106] Wherein, the preparation method of modified graphene oxide is as follows:

[0107] 10 g of graphene oxide was ultrasonically dispersed in 150 g of deionized water, 4 g of sodium carboxymethyl cellulose was added, and the mixture was stirred and mixed evenly. Then 5 g of gelatin was added, and the mixture was stirred at 85° C. for 4 h, and then ultrasonically dispersed for 30 min. The mixture was freeze-dried in vacuum and ground through a 1200 mesh sieve to obtain modified graphene oxide.

[0108] S2. The graphene composite fiber and the polyester fiber are mixed in a mass ratio of 1:1, and then interwoven by warp yarn and weft yarn, wherein the linear density of the warp yarn is 20tex, and the linear density of the weft yarn is 15tex; the specific weaving process is: the warp yarn and the weft yarn are interwoven one above and one below to form a plain weave, the warp yarn density is 360 yarns / 10cm, and the weft yarn density is 325 yarns / 10cm, to obtain a fabric base fabric;

[0109] S3, padding the fabric base fabric in the finishing liquid, the bath ratio is 1-20, the padding liquid rate of the fabric base fabric after padding is 75%, and then baking the fabric base fabric after padding, the baking temperature is 120 ° C, the drying time is 5min, and then washing with deionized water, and then drying at 60 ° C, that is, obtaining a down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 60 parts of aqueous polyurethane emulsion, 4 parts of blocked isocyanate crosslinking agent, 2 parts of modified nano-silica, 2 parts of polyhexamethylene biguanide hydrochloride, 0.5 parts of sodium dodecylbenzene sulfonate, and 10 parts of deionized water;

[0110] Wherein, the preparation method of modified nano silicon dioxide is as follows:

[0111] 8 g of nano-silica was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of vinyl triethoxysilane was added thereto, stirred at room temperature for 1 h, filtered, washed, and dried to obtain vinyl-modified nano-silica;

[0112] 5 g of vinyl-modified nano-silica was dispersed in 100 mL of organic solvent DMF, and then 2 g of terminal hydroxyl polybutadiene and 0.5 g of benzoyl peroxide were added thereto. The mixture was heated and stirred at 60°C for 5 h. After the reaction was completed, the modified nano-silica was obtained by filtering, washing, drying, and grinding through a 1200 mesh sieve.

[0113] Compared with Example 1, in Comparative Example 4, the graphene oxide aerogel was not grafted with tetraphenylethylene.

[0114] The fabrics prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the fabric sample size was 300 mm×300 mm. The specific steps were as follows:

[0115] Thermal storage and heating performance test: fabric samples were tested at 20℃ and 65% relative humidity. A xenon arc lamp was used as the irradiation light source. The sample was irradiated with 500W light for 15 minutes at a distance of 50cm above the center of the sample. The sample temperature was tested with a temperature sensor, and the temperature of the sample after 15 minutes of irradiation was recorded.

[0116] Then, the fabric samples were washed 50 times with reference to the washing method of the washing color fastness tester, and the thermal storage and heating performance of the fabric samples were retested; the test results are shown in Table 1.

[0117] Table 1 Thermal storage performance test results

[0118]

[0119]

[0120] Wear resistance test: refer to GB / T 21196-2007 "Determination of abrasion resistance of fabrics by Martindale method" standard, use YG401 flat grinder under standard three-level atmospheric pressure, with a pressure hammer of 250g and 240 grains / cm 2 Sandpaper, 300 revolutions, weigh the mass before and after grinding using an analytical balance, and calculate the mass wear loss (mg);

[0121] Then, the fabric samples were washed 50 times with reference to the washing method of the washing color fastness tester, and the wear resistance of the fabric samples was retested; the test results are shown in Table 2.

[0122] Table 2 Wear resistance test results

[0123]

[0124] Antibacterial performance test: According to the test method of GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the fabric samples prepared in Examples 1-3 were tested for antibacterial properties, and the tested bacteria were Escherichia coli;

[0125] Then, the fabric samples were washed 50 times with the washing method of the washing color fastness test machine as a reference, and the antibacterial properties of the fabric samples were retested; the test results are shown in Table 3.

[0126] Table 3 Antibacterial performance test results

[0127]

[0128] It can be seen from Table 3 that the fabric prepared by the present invention still has good antibacterial properties after being washed multiple times.

[0129] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A method for preparing a down jacket fabric containing graphene fibers, characterized in that: The steps include: S1, mixing modified graphene oxide, maleic anhydride grafted SEBS and nylon chips, extruding and granulating to obtain masterbatch, and then melt spinning to obtain graphene composite fibers; S2, mixing the graphene composite fiber and the polyester fiber, and then interweaving the warp yarn and the weft yarn to obtain a fabric base fabric; S3. The fabric base cloth is immersed in a finishing liquid for padding treatment, and then the immersed fabric base cloth is baked, washed and dried to obtain a down jacket fabric, wherein the finishing liquid comprises the following components in parts by weight: 60-80 parts of an aqueous polyurethane emulsion, 4-8 parts of a blocked isocyanate cross-linking agent, 2-4 parts of modified nano-silica, 2-4 parts of polyhexamethylene biguanide hydrochloride, 0.5-1 parts of sodium dodecylbenzene sulfonate, and 10-15 parts of deionized water.

2. The preparation method according to claim 1, characterized in that: In step S1, the preparation method of modified graphene oxide is as follows: S11, ultrasonically dispersing graphene oxide in deionized water, adding sodium carboxymethyl cellulose, stirring and mixing evenly, then adding gelatin, stirring at 85-90° C. for 2-4 hours, ultrasonically dispersing for 30-60 minutes, vacuum freeze-drying, grinding and sieving, to obtain a composite graphene oxide aerogel; S12, dispersing the composite graphene oxide aerogel in an ethanol aqueous solution, then adding vinyl triethoxysilane thereto, stirring at room temperature for 1-2 hours, filtering, washing, and drying to obtain a vinyl-modified composite aerogel; S13, dispersing the vinyl modified composite aerogel in toluene, then adding tetraphenylethylene and benzoyl peroxide thereto, heating and stirring at 70-90° C. for reaction for 3-5 hours, and after the reaction is completed, filtering, washing, drying, grinding and sieving to obtain modified graphene oxide.

3. The preparation method according to claim 2, characterized in that: In step S11, the mass ratio of graphene oxide, sodium carboxymethyl cellulose and gelatin is 10-15:4-8:5-10.

4. The preparation method according to claim 2, characterized in that: In step S12, the mass ratio of the composite graphene oxide aerogel to vinyltriethoxysilane is 10-15:1-3.

5. The preparation method according to claim 2, characterized in that: In step S13, the mass ratio of the vinyl-modified composite aerogel, tetraphenylethylene and benzoyl peroxide is 8-12:3-6:0.5-1.

6. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of modified graphene oxide, maleic anhydride grafted SEBS and nylon slices is 3-6:1-2:

100.

7. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the graphene composite fiber to the polyester fiber is 1-2:1-2.

8. The preparation method according to claim 1, characterized in that: In step S3, the preparation method of modified nano-silicon dioxide is as follows: S31, dispersing 8-12 parts of nano-silica in an ethanol aqueous solution, then adding 1-3 parts of vinyltriethoxysilane thereto, stirring at room temperature for 1-2 hours, filtering, washing, and drying to obtain vinyl-modified nano-silica; S32, dispersing vinyl modified nano silica in an organic solvent DMF, then adding terminal hydroxyl polybutadiene and benzoyl peroxide thereto, heating and stirring at 60-80°C for reaction for 2-5h, after the reaction is completed, filtering, washing, drying, grinding and sieving to obtain modified nano silica.

9. The preparation method according to claim 8, characterized in that: In step S32, the mass ratio of vinyl-modified nano-silica, terminal hydroxyl polybutadiene and benzoyl peroxide is 5-10:2-4:0.5-1.

10. A down jacket fabric containing graphene fibers prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of graphene antibacterial down jacket fabric

    CN113995189A

  • Preparation method of nano-silica surface grafted hydroxyl terminated polybutadiene rubber

    CN104962111A

  • Preparation method of graphene-chinlon nano-composite fibers

    CN105862158A

  • Preparation method of composite aerogel with high mechanical strength

    CN109293982A

  • Tensile polyamide fiber and preparation method thereof

    CN117604676A

Cited By

  • Graphene-based wear-resistant outdoor jacket fabric and preparation method thereof

    CN120867087A